Role of thoracoscopy in the management of various foregut duplication cyst (Bangladesh Journal of Endosurgery, 2013)
Aim: To highlight the role of thoracoscopy in the management of various foregut duplication cyst.Introduction: Foregut duplications are rare pathology including esophageal and bronchogenic cysts. The diagnosis is most often made from an incidental finding on chest radiograph, respiratory distress or failure to thrive. Treatment consists of complete resection by thoracotomy or thoracoscopy. We present our experience with the management of 4 cases that were managed thoracoscopically.Materials and Methods: From March 2008 to August 2011, 4 patients underwent thoracoscopy for resection of foregut duplication cyst. All the cysts were on the right side and were performed with three or four ports. The masses were removed after decompressing the cyst and enlarging one of the port sites. Chest tubes were placed in all patients.Results: All the 4 cases underwent successful thoracoscopic resection. Two cases were esophageal duplication cyst out of which one was a neuro enteric cyst, extending from the apex to the esophageal hiatus and one had common wall with the esophagus. Two cases were bronchogenic cyst. Histopathology demonstrated gastric mucosa in the neuro enteric duplication cyst. There were no complication or recurrence till date in any of these cases. onclusion: Thoracoscopic resection is a safe and an effective method for treating foregut duplication cyst. Outcomes have been good with no morbidity or mortality even in cases extending through the whole length of thorax, which would otherwise need an extended thoracotomy. Thoracoscopic resection should be considered the first line of management for these benign masses.DOI: http://dx.doi.org/10.11593/bje.2013.0101.0003Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 9-12